2019
DOI: 10.1155/2019/4383258
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Decreased Nucleolar PARP-1 as an Early Marker of Cognitive Impairment

Abstract: Poly(ADP-ribose) polymerase-1 (PARP-1) is a nuclear protein that regulates gene expression through poly(ADP)-ribosylation, resulting in the loosening of chromatin structure. PARP-1 enzymatic activity has been shown to be necessary for the expression of several genes required for memory formation and consolidation. Previously, we showed that nucleolar PARP-1 is significantly decreased in hippocampal pyramidal cells in Alzheimer's disease (AD). We proposed that the displacement of PARP-1 from the nucleolus resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The random forest model of the predominant taxa in the fecal microbiota used to identify DS in our study had similar area under the ROC curve as previous studies [ 22 ]. The KEGG pathway of ribosomal biogenesis is enriched in DS and is closely related to cognitive impairment [ 32 , 33 ], Allen et al reported that transient disruption of ribosome biogenesis could cause memory impairment [ 34 ], whereas persistent severe disruption can lead to cell death due to insufficient protein synthesis [ 35 , 36 ]. Therefore, gut microbiota alterations may also affect cognitive function via the ribosomal biogenesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The random forest model of the predominant taxa in the fecal microbiota used to identify DS in our study had similar area under the ROC curve as previous studies [ 22 ]. The KEGG pathway of ribosomal biogenesis is enriched in DS and is closely related to cognitive impairment [ 32 , 33 ], Allen et al reported that transient disruption of ribosome biogenesis could cause memory impairment [ 34 ], whereas persistent severe disruption can lead to cell death due to insufficient protein synthesis [ 35 , 36 ]. Therefore, gut microbiota alterations may also affect cognitive function via the ribosomal biogenesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The KO of TRPM2 suppressed microglial activation in the APP/PS1 transgenic AD mouse model (Ostapchenko et al, 2015) and involvement of astrocytic PARP-1 is also described by Aβ damage (Abeti and Duchen, 2012;Angelova and Abramov, 2014). Furthermore, recent evidence shows a reduced level of PARP-1 nucleolar immunohistochemical staining in hippocampal pyramidal cells in AD and MCI patients (Regier et al, 2019). These findings strongly support a key role for PARP-1 in Parthanatos, mitochondrial function and inflammation occurring in AD.…”
Section: Parp-1 and Its Role In Cell Death Mitochondrial Function Amentioning
confidence: 55%
“…Since PARP1 activation has been detected both upstream and downstream of Aβ, activation of PARP1 is implicated as an early and essential event in the pathogenesis of AD [ 208 ]. Furthermore, PARP1 reduction in the nucleus, leading to activation of DNA cytosine-5-methyltransferase 1 and silencing of nucleolar rRNA gene (rDNA), was implicated as an early marker of cognitive impairment in AD [ 209 ]. These studies therefore provide evidence that dysregulation of PARP1 is a consistent feature of AD, thus implicating parthanatos in neuronal death in this condition.…”
Section: Mechanisms Of Cell Death Induced By Dna Damage In Neurodegen...mentioning
confidence: 99%